Prediction of whole‐genome risk for selection and management of hyperketonemia in Holstein dairy cattle. (June 2017) - Weigel, K.A.; Pralle, R. S.; Adams, H.; Cho, K.; Do, C.; White, H.M.
Summary: Hyperketonemia (HYK), a common early postpartum health disorder characterized by elevated blood concentrations of β‐hydroxybutyrate (BHB), affects millions of dairy cows worldwide and leads to significant economic losses and animal welfare concerns. In this study, blood concentrations of BHB were assessed for 1, 453 Holstein cows using electronic handheld meters at four time points between 5 and 18 days postpartum. Incidence rates of subclinical (1.2 ≤ maximum BHB ≤ 2.9 mmol/L) and clinical ketosis (maximum BHB ≥ 3.0 mmol/L) were 24.0 and 2.4%, respectively. Variance components, estimated breeding values, and predicted HYK phenotypes were computed on the original, square‐root, and binary scales. Heritability estimates for HYK ranged from 0.058 to 0.072 in pedigree‐based analyses, as compared to estimates that ranged from 0.071 to 0.093 when pedigrees were augmented with 60, 671 single nucleotide polymorphism genotypes of 959 cows and 801 male ancestors. On average, predicted HYK phenotypes from the genome‐enhanced analysis ranged from 0.55 mmol/L for first‐parity cows in the best contemporary group to 1.40 mmol/L for fourth‐parity cows in the worst contemporary group. Genome‐enhanced predictions of HYK phenotypes were more closely associated with actual phenotypes than pedigree‐based predictions in five‐fold cross‐validation, and transforming phenotypes to reduce skewness and kurtosis also improved predictive ability. This study demonstrates the feasibility of using repeated cowside measurement of blood BHB concentration in early lactation to construct a reference population that can be used to estimate HYK breeding values for genomic selection programmes and predict HYK phenotypes for genome‐guided management decisions.